Factors Influencing User Preference For E-Wallets vs. Traditional Payments Methods - Kok Ban Teoh; Anees Janee Ali; Nur Fathin Balqis Binti Ahmad Sukri; Nur Aziyanny Binti Abdullah; Nur Damia Binti Shuazman; Nur Dianah Azwa Binti Shaharuddin; Nur Farisyazliana Binti Fauzi; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
E-wallets are digital payment systems that allow users to make contactless transactions through smartphones or computers, offering convenience and efficiency, particularly for remote payments. Traditional payment methods, such as cash, checks, and card swipes, are perceived as more secure and reliable but may lack the flexibility of digital options. This study compares user experiences between e-wallets and traditional payment methods, focusing on perceived ease of use, convenience and usability, privacy and security, and satisfaction. A quantitative approach, utilizing an online survey of 100 respondents, is used to evaluate user preferences. The study aims to identify key factors influencing payment method choice, providing insights that could guide improvements in payment technologies and enhance user experiences for both consumers and businesses.